THE EFFECTS OF GENDER AND EDUCATION LEVEL OF THE EMPLOYEE ON THE PSYCHOLOGICAL CAPITAL PERCEPTIONS (Third Sector Social Economic Review, 2017)
A human being is the most valuable asset in the organizations. Man is the planner and executive of processes with knowledge, experience, talent and expertise. It is very important for employees to feel happy in their work processes, to love their work, and to adopt the organization. It is aimed to develop and improve the qualifications of the individuals working with psychological capital. Organizational performance will be positively impacted by the development of individuals' hopes, optimism, self-sufficiency and psychological endurance. In an organization, there are employees of different gender groups as men and women, and their level of education may differ from each other. In this study, effects of gender and education level on psychological capital perceptions of employees were investigated. The target population of the study is 252 working in a public institution in Ankara. Judicial and easy sampling techniques and data obtained from 101 employees were included in the research. The data were collected on a cross-sectional basis using the likert scale previously prepared. In order to investigate the construct validity of psychological capital scale, first level multi-factor confirmatory factor analysis was performed with AMOS 22 program. The cronbach alpha coefficients were calculated by SPSS 22 program to determine the reliability of the scale. The scale was found to be reliable. As a result of the findings, it was seen that gender and education level had no effect on psychological capital perceptions of employees.
Keywords: Psychological Capital; Gender; Educational Level